The marketing analytics practitioner's guide volume 1 : brand and consumer - Charan, Ashok (Singapore : World Scientific Publishing Co. Pte. Ltd., 2024)
"As the use of analytics becomes increasingly important in today's business landscape, The Marketing Analytics Practitioner's Guide (MAPG) provides a thorough understanding of marketing management concepts and their practical applications, making it a valuable resource for professionals and students alike. The four-volume compendium of MAPG provides an in-depth look at marketing management concepts and their practical applications, equipping readers with the knowledge and skills needed to effectively inform daily marketing decisions and strategy development and implementation. It seamlessly blends the art and science of marketing, reflecting the discipline's evolution in the era of data analytics. Whether you're a seasoned marketer or new to the field, the MAPG is an essential guide for mastering the use of analytics in modern marketing practices. Volume I is focused on Brand and Consumer. Part I of this volume is dedicated to understanding the concepts and methods of brand sensing and brand equity. It delves into the analytic techniques used to track and profile brand image, and explains the key components of brand equity, how to measure it, and what factors drive it. It provides readers with a comprehensive framework for measuring and understanding brand equity and the tools to pursue its growth. Part II of this volume focuses on understanding consumers through qualitative and quantitative research methods, segmentation, customer satisfaction, customer value management, consumer panels, consumer analytics and big data. The volume covers the analytic tools used to extract insights from consumer transactions, which are becoming increasingly important in today's data-driven world. It also covers the use of consumer analytics and big data specifically within consumer markets"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Branding (Marketing).; Marketing research -- Data processing; Customer equity; Quantitative research